Proteinuria is Associated with Neurocognitive Impairment in Antiretroviral Therapy Treated HIV-infected Individuals - Kalayjian, Robert C. (2014)
BACKGROUND: Proteinuria is a marker of vascular dysfunction that predicted increased cardiovascular mortality, and was associated with neurocognitive impairment (NCI) in population-based studies. We examined associations between proteinuria and HIV-associated NCI. METHODS: Multivariable logistic regression was used to examine associations between NCI at the first neurocognitive assessment (baseline) and simultaneous, clinically significant proteinuria (as random spot urine protein-to-creatinine ratios [UP/Cr] ≥ 200 mg/g) in a prospective multicenter observational cohort study. Generalized estimating equations were used to examine associations between baseline proteinuria and subsequent NCI among subjects without NCI at baseline. NCI was defined as a z-score, derived from the combination of normalized scores from the Trailmaking A & B and the Wechsler Adult Intelligence Scale-Revised Digit Symbol tests. RESULTS: 1,972 subjects were included in this analysis. Baseline proteinuria was associated with increased odds of NCI (OR: 1.41 [95% C.I., 1.08 to 1.85]; P=0.01), and with subsequent NCI among subjects without NCI at baseline (OR=1.39 [95% C.I., 1.01 to 1.93], P=0.046) in multivariable models adjusted for risk factors and potential confounders. Similar associations were evident when these analyses were limited to visits at which time study subjects maintained plasma HIV RNA levels < 200 copies/mL. CONCLUSIONS: The association between proteinuria and NCI observed in this study adds to a growing body of evidence implicating contributions by vascular disease to NCI in antiretroviral treated individuals. Studies examining interventions that improve vascular function are warranted.